What matters for people with brain cancer? Selecting clinical quality indicators for an Australian Brain Cancer Registry. Issue 1 (31st August 2021) - Matsuyama, Misa; Sachchithananthan, Mythily; Leonard, Robyn; Besser, Michael; Nowak, Anna K; Truran, Donna; Vajdic, Claire M; Zalcberg, John R; Gan, Hui K; Gedye, Craig; Varikatt, Winny; Koh, Eng-Siew; et al.
Abstract: Background: The goal of a clinical quality registry is to deliver immediate gains in survival and quality of life by delivering timely feedback to practitioners, thereby ensuring every patient receives the best existing treatment. We are developing an Australian Brain Cancer Registry (ABCR) to identify, describe, and measure the impact of the variation and gaps in brain cancer care from the time of diagnosis to the end of life. Methods: To determine a set of clinical quality indicators (CQIs) for the ABCR, a database and internet search were used to identify relevant guidelines, which were then assessed for quality using the AGREE II Global Rating Scale. Potential indicators were extracted from 21 clinical guidelines, ranked using a modified Delphi process completed in 2 rounds by a panel of experts and other stakeholders, and refined by a multidisciplinary Working Group. Results: Nineteen key quality reporting domains were chosen, specified by 57 CQIs detailing the specific inclusion and outcome characteristics to be reported. Conclusion: The selected CQIs will form the basis for the ABCR, provide a framework for achievable data collection, and specify best practices for patients and health care providers, with a view to improving care for brain cancer patients. To our knowledge, the systematic and comprehensive approach we have taken is a world first in selecting the reporting specifications for a brain cancer clinical registry.